Does gender disparity in financial literacy still persist after retirement? Evidence from Ghana. Issue 1 (8th January 2018) - Adam, Anokye M.; Boadu, Mavis Opoku; Frimpong, Siaw
Abstract : Purpose: The purpose of this paper is to examine the gender disparity in financial literacy among retirees in the Cape Coast metropolis in Ghana. Design/methodology/approach: The finding of this paper is based on 334 respondents (183 males and 151 females) to financial literacy questionnaires covering the respondents' general knowledge on budgeting, use of automated teller machine, time value of money, account types, cheque handling and insurance. Data were analysed with Pearson χ 2 and independent sample t -test. Findings: Nominal scores showed that male domination in financial literacy in seven out of the ten questions used to assess financial literacy while female retirees lead in three. These observed nominal differences were, however, found not to be significant through χ 2 test of independence except the question on the calculation of interest rate on loans in favour of males. The cumulative effect, through computation of financial literacy index was deemed to be significantly different between males and females, favouring males, using independent sampled t -test. Practical implications: The implication is that older men continue to have their financial literacy hegemony perpetually and are stronger in computational ability. It suggests that policy responses to address gender disparity in financial literacy should work more on computational ability of females. Originality/value: There is no known study of financial literacy related to gender disparity in Ghana.